Excess winter mortality patterns and regional differences in Portugal - Freire, Elisabete (2013)
The mortality fluctuation over the year is associated with increases in both the warm and cold seasons. Portugal is often described as the European country with highest excess winter mortality. The main aim of this study is to identify the seasonal patterns of mortality within Portugal and to assess their geography. The chi-square goodness of fit test was used to identify the existence of a significant seasonal increase in mortality by cause of death. The number of excess winter deaths and the excess winter death index were calculated to measure the winter death toll. The main results shown important seasonal mortality increases in almost all causes of death, the mortality due to cardiovascular and respiratory diseases are the main responsible for the winter burden. The number of excess winter death is related to the overall incidence of the disease and their determinants, but the seasonal increase is related to other socioeconomic and behavior factors.